O Programa Começar de Novo: uma política governamental de geração de renda - Morais, Cícera Vieira Santos de (2009)
This dissertation analyses the Program Começar de Novo , Starting Over, a governmental policy of income generation, aimed at the population of 40 years of age and over, taking part in the redistributive programs conducted by the municipality of São Paulo s Secretary of Development, Work and Solidarity, during the mandate of the mayor Marta Suplicy, from January 2001 to December 2004. It also works with the notions of globalization, professional qualification, competences and citizenship, which are the guiding principles of this governmental policy. Moreover, it analyses the metamorphoses of the contemporary world of work, understood as the whole of the changes in the production and management of the working force and their effect in the unemployment rates, which have reached even the skilled and formally educated people who have certified know how . This mismatch between education and long term unemployment motivated this study. Therefore, this dissertation approaches the analysis of the program Começar de Novo/Starting Over not only in terms of the constant internal and external forces that shape it, but also in terms of the main foci and conflicts that permeate this governmental policy of income generation